2014
DOI: 10.1016/j.jcrs.2013.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of lens densitometry using Scheimpflug imaging

Abstract: Lens densitometry using Scheimpflug imaging was highly repeatable. However, repeatability was dependent on the analysis mode used. Repeatability decreased with increasing opacification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
40
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 9 publications
0
40
0
Order By: Relevance
“…This is a problem inherent in this technology that could lead to higher and false maximum values. 10 Careful analysis of previously published studies also showed the same limitation. In the present study, we used the automatic densitometry method.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…This is a problem inherent in this technology that could lead to higher and false maximum values. 10 Careful analysis of previously published studies also showed the same limitation. In the present study, we used the automatic densitometry method.…”
Section: Discussionmentioning
confidence: 88%
“…There is no consensus regarding which method and variable are the most representative of the true optical status of the lens nucleus. 10 In a previous study, 17 the maximum value assessed at a single point was found to be most likely representative of the nucleus because the nuclear cataract is regarded as a homogenous structure. Another issue is the presence of reflex artifacts in front or within the lens.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations